2019
DOI: 10.1186/s13063-019-3556-4
|View full text |Cite
|
Sign up to set email alerts
|

NA-CONTROL: a study protocol for a randomised controlled trial to compare specific outpatient rehabilitation that targets cerebral mechanisms through relearning motor control and uses self-management strategies to improve functional capability of the upper extremity, to usual care in patients with neuralgic amyotrophy

Abstract: Background Neuralgic amyotrophy (NA) is a distinct peripheral neurological disorder of the brachial plexus with a yearly incidence of 1/1000, which is characterised by acute severe upper extremity pain. Weakness of the stabilising shoulder muscles in the acute phase leads to compensatory strategies and abnormal motor control of the shoulder - scapular dyskinesia. Despite peripheral nerve recovery, scapular dyskinesia often persists, leading to debilitating residual complaints including pain and fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The RCT was powered to demonstrate clinical effects of a specialized rehabilitation programme on functional capability of the upper limb in NA patients. 35 The current sample (39 NA patients, 23 healthy participants) suffices to replicate our previous behavioural finding of a significant interaction effect of GROUP × LATERALITY on ER on the same task in an independent sample of NA patients 18 (with power at 0.90 and α at 0.05, the required sample size is 14). 37 Previous fMRI studies using the same task have found differences in brain activity between patient populations and healthy participants with sample sizes similar to the current sample.…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…The RCT was powered to demonstrate clinical effects of a specialized rehabilitation programme on functional capability of the upper limb in NA patients. 35 The current sample (39 NA patients, 23 healthy participants) suffices to replicate our previous behavioural finding of a significant interaction effect of GROUP × LATERALITY on ER on the same task in an independent sample of NA patients 18 (with power at 0.90 and α at 0.05, the required sample size is 14). 37 Previous fMRI studies using the same task have found differences in brain activity between patient populations and healthy participants with sample sizes similar to the current sample.…”
Section: Methodsmentioning
confidence: 52%
“…For an extensive description of the RCT see Lustenhouwer et al . 35 The study was approved by the local medical ethical committee (Medical Ethical Committee region Arnhem-Nijmegen, CMO 2017-3740) and is registered at ClinicalTrials.gov (NCT03441347).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 27 patients with dystonic tremor syndrome from the Radboud university medical centre (Radboudumc Nijmegen, 18 patients), Academic Medical Center (AMC Amsterdam, 7 patients), Maastricht University Medical Center+ (MUMC Maastricht, 1 patient) and Canisius Wilhelmina Ziekenhuis (CWZ Nijmegen, 1 patient). For comparison of grey matter volume with patients, we selected 27 healthy controls from two prior studies that best matched our dystonic tremor syndrome group on age and sex ( Nuland et al, 2020 , Lustenhouwer et al, 2019 ). The healthy controls were 61.0 ± 11.5 years old (range 34–80) and sex was distributed as in dystonic tremor syndrome patients (13 male, 14 female).…”
Section: Methodsmentioning
confidence: 99%
“…We included 27 patients with dystonic tremor syndrome from the Radboud university medical centre (Radboudumc Nijmegen, 18 patients), Academic Medical Center (AMC Amsterdam, 7 patients), Maastricht University Medical Center+ (MUMC Maastricht, 1 patient) and Canisius Wilhelmina Ziekenhuis (CWZ Nijmegen, 1 patient). For comparison of grey matter volume with patients, we selected 27 healthy controls from two prior studies that best matched our dystonic tremor syndrome group on age and sex 28,29 . The healthy controls were 61.0 ± 11.5 years old (range 34-80) and sex was distributed as in dystonic tremor syndrome patients (13 male, 14 female).…”
Section: Methodsmentioning
confidence: 99%